The influence of exposure approaches to in vitro lung epithelial barrier models to assess engineered nanomaterial hazard - Kirsty Meldrum (Nanotoxicology, 2022)
Exposure to engineered nanomaterials (ENM) poses a potential health risk to humans through long-term, repetitive low-dose exposures. Currently, this is not commonplace within in vitro lung cell cultures. Therefore, the purpose of this study was to consider the optimal exposure approach toward determining the stability, sensitivity and validity of using in vitro lung cell mono- and co-cultures to determine ENM hazard. A range of exposure scenarios were conducted with DQ12 (previously established as a positive particle control) (historic and re-activated), TiO2 (JRC NM–105) and BaSO4 (JRC NM–220) on both monocultures of A549 cells as well as co-cultures of A549 cells and differentiated T HP-1 cells. Cell cultures were exposed to either a single, or a repeated exposure over 24, 48- or 72-hours at in vivo extrapolated concentrations of 0–5.2 μg/cm2, 0-6 μg/cm2 and 0-1μg/cm2. The focus of this study was the pro-inflammatory, cytotoxic and genotoxic response elicited by these ENMs. Exposure to DQ12 caused pro-inflammatory responses after 48 hours repeat exposures, as well as increases in micronucleus frequency. Neither TiO2 nor BaSO4 elicited a pro-inflammatory response at this time point. However, there was induction of IL-6 after 24 hours TiO2 exposure. In conclusion, it is important to consider the appropriateness of the positive control implemented, the cell culture model, the time of exposure as well as the type of exposure (bolus or fractionated) before establishing if an in vitro model is appropriate to determine the level of response to the specific ENM of interest.